Emphysematous pyelonephritis: non surgical treatment approach - Singal, Kiran Kumar; Singal, Neerja; Gupta, Bhaskar; Bhatti, Karun Puran; Gupta, Abhinav (Bangladesh Journal of Medical Science, 2015)
Emphysematous pyelonephritis is a severe infection characterized by the presence of gas within the renal parenchyma tissues. It is a life threatening complication of bacterial interstitial nephritis, and it mainly occurs in patients with diabetes mellitus. We report a case of a 37 year old female who complained of fever and pain in left lumbar region on admission. Her past medical history included uncontrolled type 2 diabetes mellitus. On USG (ultrasonography), left kidney swollen and show echogenic linear specs with dirty shadowing suggestive of air in pelvicalyceal system (PCS). She was treated with intensive antibiotic therapy in high doses. On repeat USG there was marked reduction in air shadow in kidney and patient improved clinically. Bangladesh Journal of Medical Science Vol.14(3) 2015 p.305-307